Diagnosis of managerial competencies of Costa Rican archivists - Zamora Guzmán, Katia (2014)
Now days the role of the archivist in public institutions is strategic and adds value to the development of the mission of such institutions. Due to the importance of the above, a diagnose of management competencies was performed, based on a query made with a survey to personnel responsible for managing the central archives of the Costa Rican public sector. The objective of this paper is to present the results of the study performed. Some of the results that this diagnosis showed are that respondents agreed that those responsible for central files should be considered managers, thus requiring management skills to their performance. However, half of respondents considered that the training in the career of Archives at the Universidad de Costa Rica, does not provide the required training to manage a central archive, given this fact the respondents proposed to be give a managerial approach to this career.